RIVERBANK PROTECTION STRUCTURE FAILURE FACTORS AND REMEDIAL APPROACH: A CASE STUDY IN KELANTAN MALAYSIA - Kay Leng, See Too; Ata, Frankie Marcus; Jaafar, Mokhtar; Torima, Mohd Ekhwan; Kamarudin, Mohd Khairul Amri (PLANNING MALAYSIA, 2023)
Numerous structural mitigation measures have been implemented to ensure the sustainability of socio-environmental systems. Riverbank erosion can be avoided through the installation of reinforced walls, groynes, and sheer piles, among other measures. However, these structures sometimes fail to protect riverbanks from collapsing due to various factors, including environmental and anthropogenic influences. Therefore, this study aims to identify the factors contributing to the failure of riverbank protection structures and determine remedial approaches to enhance them. The study utilized a combination of site visits, document analysis, and interviews with riverbank protection structure engineers and contractors to gather the necessary information to achieve study objectives. The study found that geomorphology; hydraulics; and unstable sheet pile construction were the factors to the riverbank failure. Besides, study also recommend the suitable remedial approach in terms of design; construction and maintenance to build a stable riverbank protection structure (rock embankment). The findings of this study can contribute to the development of more effective and sustainable riverbank protection measures, which are essential to protect vulnerable communities and ecosystems from the impacts of environmental hazards. The study's results can guide policymakers, engineers, and other stakeholders involved in riverbank protection to better understand the factors that contribute to structure failure and how to mitigate these risks. It can also contribute to the advancement of knowledge in the field of riverbank protection, specifically in identifying the most effective mitigation strategies.